Effects of neutron irradiation and post-irradiation annealing on the microstructure of HT-UPS stainless steel - Xu, Chi; Chen, Wei-Ying; Zhang, Xuan; Wu, Yaqiao; Li, Meimei; Yang, Yong (Journal of nuclear materials, 2018)
Microstructural changes resulted from neutron irradiation and post-irradiation annealing in a high-temperature ultra-fine precipitate strengthened (HT-UPS) stainless steel were characterized using transmission electron microscopy (TEM) and atom probe tomography (APT). Three HT-UPS samples were neutron-irradiated to 3 dpa at 500 °C, and after irradiation, two of them were annealed for 1 h at 600 °C and 700 °C, respectively. Frank dislocation loops were the dominant defect structure in both the as-irradiated and 600 °C post-irradiation-annealed (PIAed) samples, and the loop sizes and densities were similar in these two samples. Unfaulted dislocation loops were observed in the 700 °C PIAed sample, and the loop density was greatly reduced in comparison with that in the as-irradiated sample. Nano-sized MX precipitates were observed under TEM in the 700 °C PIAed sample, but not in the 600 °C PIAed or the as-irradiated samples. The titanium-rich clusters were identified in all three samples using APT. The post-irradiation annealing (PIA) caused the growth of the Ti-rich clusters with a stronger effect at 700 °C than at 600 °C. The irradiation caused elemental segregations at the grain boundary and the grain interior, and the grain boundary segregation behavior is consistent with observations in other irradiated austenitic steels. APT results showed that PIA reduced the magnitude of irradiation induced segregations.